Niches in derivational morphology: specialisation of suffixes within the formation of Portuguese deverbal nouns - Rodrigues, Alexandra Soares (2017)
The aim of this paper is to study the specialisation of affixes following the same word-formation rule/schema. The derivational morphology of Portuguese presents a multiplicity of suffixes that create deverbal nouns with the general meaning of ‘event’/’result’/’state’ (Rodrigues 2008). Those suffixes may be exemplified by -ção (avaliação ‘evaluation’), -mento (congelamento ‘freeze’), -dura (raladura ‘event of grating’), -agem (aterragem ‘landing’), -nça (cobrança ‘levy’), -ão (empurrão ‘push’), -nço (falhanço ‘failure’), -ido (ladrido ‘barking’), -ice (coscuvilhice ‘gossip’), etc. Apparently, those suffixes are rivals, because all of them generate the same kind of products from the same kind of bases. According to the Darwinist perspective presented by Lindsay & Aronoff (2013), Aronoff & Lindsay (2014, 2015) and Aronoff (2016), two affixes that are in mutual competition would either lead to the annihilation of one of them, or they may survive in the language with the condition that they find a niche, i.e. a specialisation. In this paper, we will focus on the differences between the suffixes -dura, mento and -ido, specifically with respect to their selectional restrictions and the secondary meanings of ‘state’ and ‘concrete result’ of the respective deverbal nouns. The analysis of those meanings is based on the exploration of corpora (Corpus do Português, Corpus de Referência do Português Contemporâneo, Corpus Informatizado do Português Medieval). Although the three suffixes produce event/result/state nouns (in some cases from the same verbal base), the meanings of ‘concrete result’ of products with dura mainly designate ‘wounds’, ‘portions’ and ‘residues’ (maçadura ‘bruise’, envergadura ‘wingspan’, serradura ‘sawdust’). Nouns with the suffix -ido indicate sounds (rosnido ‘snarl’, ronquido ‘snore’). These properties are the result of specialisations of each one of the suffixes that do not characterise the other suffixes. Apart from the meaning differences, the niches of the suffixes are also based on their selectional restrictions: -ido only operates with unergative verbs of emission of sound; -dura shows a preference towards verbs of causation with the meaning of ‘to reduce to fragments’, which goes back to medieval Portuguese, as observable in the analysis of the lexicon of veterinary treatises, as Giraldo (1318). The analysis of the niches or specialisations of suffixes with the same word formation rule/schema is consistent with the idea that word formation is a dynamic domain which is dependent on patterns that speakers deduce from the language usage. A word-formation rule/schema may be seen as a macro-pattern, for which the relation between the category of the base, the category of the product and the meaning of the latter builds the pattern. In this sense, event/result/state deverbal nouns correspond to a macro-pattern. Within those macro-patterns, micro-patterns may be observed. Those micro-patterns correspond to the niches of each suffix operating within the same macro-pattern. Micro-patterns are built, among other factors, according to selectional restrictions that regulate the adjunction of affixes to bases and according to the possible general and secondary meanings of the products of each one of the suffixes. For instance, the specialisation of the suffix -ido concerning both the meaning of ‘sound’ and its selectional restrictions constitutes a micro-pattern within the macro-pattern of event/result/state deverbal nouns.